LA DEUDA HISTÓRICA DEL BICENTENARIO EL DERECHO INDÍGENA PERUANO, VISTO DESDE EL SUR - ESPEZUA SALMON, BORIS GILMAR (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2020)
It is about showing that at the beginning of the 20th century in the south of Peru, and particularly in Puno, a concern for Peruvian indigenous Law arose and now, regarding the 200th anniversary of the Republic that we are about to celebrate, it is worth remembering what motivations had the promoters of this proposal, what activities they developed, what kind of resonance had their contributions in the national spectrum. The present work, in addition, is part of the historical debts that the country has had, in many issues that it has left aside , which you have neglected, or have deliberately not paid due attention to. One of them is precisely the issue of original, indigenous, ancestral Law that is now approached as intercultural justice, or legal pluralism, and that is just beginning to be treated as a new theory and trend that should deserve a place in the construction of a new country in the coming years.